Circulating Exosome microRNAs as Diagnostic Biomarkers of Dementia - Dong, Xiaoyu; Zheng, Dongming; Nao, Jianfei (Frontiers in Aging Neuroscience, 2020)
Dementia is a syndrome with acquired cognitive impairment at its core that leads to a significant decline in a patient’s daily life, learning, and ability to communicate with others. Many diseases cause dementia, with common ones that include: Alzheimer’s disease, dementia with Lewy body, frontotemporal dementia, and Parkinson’s disease dementia. Although biomarkers in cerebrospinal fluid and peripheral blood physicochemical analysis methods can indicate neurological impairment, there are currently no sensitive biomarkers that can be used for the early clinical diagnosis of dementia and for identifying the cause of dementia. Circulating micro (mi)RNAs have been suggested in previous studies as diagnostic biomarkers for diagnosing neurological disorders. However, they are susceptible to interference by other components in the peripheral circulation, making researchers question the diagnostic value of circulating miRNAs. The exosomes secreted by most cells in the body contain proteins, mRNAs, and miRNAs that are closely associated with changes in their cellular functions. Exosome miRNAs (ex-miRNAs) are highly stable and resistant to degradation, suggesting these may be an appropriate biomarker for the early clinical diagnosis of dementia. Here, we reviewed studies of ex-miRNAs that commonly cause clinical dementia disorders, and explored whether ex-miRNAs could be used as early diagnostic biomarkers in dementia.